Towards a New Human Trafficking Strategy: Proactivity at the Heart of the Ps Paradigm - van Rij, J.J.M. (International Journal of Criminology and Sociology, 2023)
For years the main approach in the fight against human trafficking has been that of the four P paradigm. Prevention, protection, prosecution, and partnerships have been leading the way for many working in the field of anti-human trafficking. Prevention being the primary goal as the anti-trafficking movement aims for a total eradication of the crime itself. Protection is aimed at strengthening the position of the victim by reducing risk and by making resocialisation possible. Improving the success rate of the prosecution of human traffickers should help deter the crime from happening and foresee in reparations for the victims involved. Partnerships are a means as human trafficking is a crime that effects all and therefore all should take responsibility in the fight against human trafficking. Even though this paradigm shapes the fight against human trafficking, the effects differ over time and location but the (positive) effects are seemingly decreasing. The crime of human trafficking, due to the legal construction of its definition, continues changing strategies fuelled by international advising bodies, change in leadership and challenges in focus requires necessary adaptivity in vision and work in order to remain successful in the fight against human trafficking. One of the ways to adapt is to have a better information position on how human trafficking in its many types manifests itself within society. This can be done by explaining the applied modus operandi, assessing the nature and extend of the crime and continuously rethinking the effectivity of prevention and prosecution. In that sense the four P paradigm needs a well-earned update which conceptualizes the possibilities of the implementation of the four P paradigm in practice by using the knowledge of the results and effects from the past. The way forward is that of bringing the four P paradigm out of its reactive way of how it is currently being implemented and used and by applying pro-activity at the centre of each of the four Ps to renew their worth and move back to the initial goals of the paradigm, knowingly that of an effective comprehensive integrated approach to fight human trafficking. To support this step forward, this article examines each of the four Ps and tries to take them out of the reactive way in which they are currently being used and into a proactive implementation of thoughts, ideas and methods for different partners involved in the fight against human trafficking. This article discusses the necessity of the change to a proactive approach in support of the goals of the Ps paradigm and by using practical examples it tries to give insight in what is possible within the current conditions and available means. At the same time, it gives constructive criticism of some fundamental elements within the fight against human trafficking and the use of the four P paradigm.